Criminal Responsibility of Corporations in Criminal Acts of Corruption - Nani Widya Sari; Oksidelfa Yanto; Suhendar; Samuel Soewita; Henny Nuraeny (IJOLARES: Indonesian Journal of Law Research, 2025)
At this time, the existence of corporations is felt to be increasingly important and strategic, in addition to being able to help turn the wheels of the economy, corporations have also reached almost all spheres of life. Corporations do not only carry out activities that aim to achieve their goals based on the provisions of the laws and regulations that govern them but in certain cases, many corporations commit criminal acts of corruption. Corruption is developing in various sectors, including state-owned companies.  The purpose of this study is to determine the criminal liability of corporations in the crime of corruption. The research method used is normative juridical, where this research was conducted by examining library materials in the form of secondary data obtained from various legal materials. The research results show the law must be interpreted as a regulation that is real and applies to all humans without exception. All acts of corruption committed by corporations must be subject to sanctions if they are contrary to applicable legal regulations. So that the law will function in order to achieve the objectives of the law, namely certainty, justice and benefit.  That that corporations are responsible as legal subjects in criminal acts of corruption. Legal subjects are not only individuals or individuals but legal entities such as corporations that can be held accountable. The existence of an error is an absolute element that can result in a corporation being held criminally responsible.